Surface electroencephalographic neurofeedback improves sustained attention in ADHD: a meta-analysis of randomized controlled trials - Hsien‐Jane Chiu; Cheuk-Kwan Sun; Hsin-Yi Fan; Ruu‐Fen Tzang; Ming-Yu Wang; Ying-Chih Cheng; Yu-Shian Cheng; Pin-Yang Yeh; Weilun Chung (BMC, 2022)
Abstract Background The efficacy of surface electroencephalographic neurofeedback (EEG-NF) for improving attentional performance assessed by laboratory measures in patients with attention-deficit/hyperactivity disorder (ADHD) remains unclear. Methods Following the PRISMA guidelines, the PubMed, Embase, ClinicalKey, Cochrane CENTRAL, ScienceDirect, Web of Science, and ClinicalTrials.gov databases were systematically searched for randomized controlled trials on the efficacy of surface EEG-NF against ADHD focusing on attentional performance evaluated by laboratory measures from inception to January 2022. Results Fourteen eligible studies were analyzed. Of the 718 participants involved, 429 diagnosed with ADHD received EEG-NF treatment. Significant improvement in attentional performance in ADHD subjects receiving EEG-NF was noted compared to their comparators (p < 0.01). Besides, there was a significant EEG-NF-associated beneficial effect on sustained attention (Hedges' g = 0.32, p < 0.01), whereas the impact on selective attention (p = 0.57) and working memory (p = 0.59) was limited. Moreover, protocol including beta wave enhancement was superior to that only focusing on reducing theta/beta ratio or modulation of slow cortical potential. Subgroup analyses showed that three sessions per week of EEG-NF produced the best effect, while the efficacy of surface EEG-NF was much poorer (Hedges' g = 0.05) when only studies that blinded their participants from knowledge of treatment allocation were included. No significant difference was noted in the improvement of attentional performance 6-12 months after EEG-NF intervention (n = 3, p = 0.42). Conclusions Our results demonstrated the satisfactory effectiveness of surface EEG-NF for improving sustained attention, especially when beta wave enhancement was included, despite its failure to sustain a long-term effect. Further large-scale trials are warranted to support our findings.